Innovations in health system finance in developing and transitional economies - Dor, Avi, 1956-; Chernichovsky, Dov; Hanson, Kara (Emerald, 2009)
Low- and middle-income countries face major challenges to their health systems. These include a high burden of communicable disease and an emerging non-communicable disease burden. Coverage of effective services and interventions is inadequate and often constrained by funding availability. At the same time, the international financing environment is changing rapidly, with new funding streams becoming available in part as a response to the challenges of meeting the Millennium Development Goals. These countries have taken a diversity of approaches to health care financing policies and programs to face the old and emerging challenges. This is increasingly accompanied by conceptual and applied research which is contributing to our understanding of how different financing mechanisms can contribute to the overall objectives of a health care system. The goal of this volume is to assemble the best of this research and synthesize 'best practices' for the benefit of researchers, policy makers and high level administrators, dealing with all elements of health care financing and focusing on both middle- and low-income settings, to represent the experiences of all regions of the developing world.
Keywords: Business & Economics -- Economics -- General.; Medical -- Health Care Delivery.; Health economics.; Health systems & services.; Medical care -- Finance.; Medical care, Cost of.; elektronické knihy; electronic books